(untitled) (Research, Society and Development, 2021)
Blood donation represents an important public health action across the country, although it has high rates of transmissibility and infection by the human immunodeficiency virus (HIV). Therefore, the present study aims to assess the epidemiological profile and HIV prevalence in individuals who donated blood at the Hematology and Hemotherapy Center of Piauí (HEMOPI), from 2008 to 2013. The study has a retrospective, descriptive character, documentary and quantitative basis. The data were provided by HEMOPI and were analyzed considering the following parameters: frequency of blood donors between the period 2008 to 2013, age group, profession, marital status, prevalence in the municipalities, color and sex. The data analysis showed that the largest number of blood donors in HEMOPI occurred in the year 2013. The state of Piauí, in the period from 2008 to 2013, presented a total of 1701 positive cases, that is, presented a frequency of 0.7%, with men being the most affected with 62.4%, while women represented 37.6% of the cases. There was also a predominance in individuals aged between 18 and 29 years old, students and with single marital status. As for ethnicity, the highest occurrence of cases was in mestizo individuals, with 1,407 seropositive in terms of geographic distribution, Teresina had a higher prevalence. Therefore, it is important to maintain and promote health education so that the population has the capacity to conduct self-care practices.